Transitory and Permanent Shocks in the Global Market for Crude Oil - Rebei, Nooman (IMF Working Papers; Working Paper ;, 2020)
This paper documents the determinants of real oil price in the global market based on SVAR model embedding transitory and permanent shocks on oil demand and supply as well as speculative disturbances. We find evidence of significant differences in the propagation mechanisms of transitory versus permanent shocks, pointing to the importance of disentangling their distinct effects. Permanent supply disruptions turn out to be a bigger factor in historical oil price movements during the most recent decades, while speculative shocks became less influential.